Assessment of Natural Radioactivity Level and Radiological Index in the Vicinity of Lynas Rare-earth Processing Plants - W.M. ZAL U’YUN; M.W. YII; K. MOHD ASHHAR; M.K. KHAIRUDDIN; I. ABDUL KADIR; Y. MOHD ABD WAHAB (ASEAN Journal on Science and Technology for Development, 2017)
The findingsof the sudy on assessment of natural radioactivity level and radiation hazard parameters in the vicinity of Lynas rare-earth processing plants are reported. This studyaims to quantify the environmental levels of natural radionuclides in soil collected in the vicinity of Lynas rare-earth processing plants and thereby to assess potential radiological hazards to the environment. About 31 terrestrialsampling locations were chosen for collection of the soil samples. The activity concentrations of the naturally occurring radioactive material (NORM) members, i.e. 226Ra, 228Ra, 238U, 232Th and 40K were measured using HpGe gamma spectrometer after reaching 30 days of secular equilibrium with their daughters. The mean activity concentration of 226Ra 228Ra 238U, 232Th and 40K in soil samples were 35 Bq/kg, 62 Bq/kg, 38 Bq/kg, 60 Bq/kg and 245 Bq/kg, respectively. The estimatedRaeq and Hex readings due to natural environmental radiation in respectively lower than the recommended value of 370 Bq/kg and unity. Meanwhile, the total air absorbed dosage rate was slightly higher than the estimatedaverage global terrestrialradiation but much lower compared to other regions in Malaysia. The results indicated that the radiation hazard in the vicinity of the Lynas rare-earth processing plants was negligible. Thus, it could be concluded that there were no additional radiation level and no radiological hazard effects to the people living in the surrounding areas.